Genre study in result and discussion section of scientific papers - Salma, Arina Mawahibi; Salsabila, Karenina Dwi; Sholikhah, Lianatus; Fadillah, Delfi Frizka; Kurniawan, Agung Budi (LINGUISTICA, 2025)
This study examines the application of genre patterns in the "Results and Discussion" section of scientific articles written by lecturers at Universitas Tidar using the Systemic Functional Linguistics (SFL) framework. Through qualitative analysis, this study identifies five main genres—descriptive, expository, prescriptive, analytical, and argumentative—that are used strategically to improve clarity, coherence, and effectiveness of communication in scientific writing. Each genre is analyzed based on its linguistic features and its contribution to fulfilling the ideational, interpersonal, and textual functions in the IMRD structure. The results of the study indicate the important role of knowledge about genres in improving the quality of academic writing, especially in conveying complex ideas, establishing credibility, and ensuring a logical flow of information. This study emphasizes the importance of implementing a genre-based approach in teaching academic writing to help students and researchers produce well-structured and impactful scientific papers. By bridging linguistic theory and practical writing strategies, this study contributes to the development of genre literacy and academic communication skills.